Twelve-month Outcomes of Dexamethasone Implant Treatment in Macular Edema Secondary to Retinal Vein Occlusion in Real Life - Abdullah Özkaya; Ipek Tanir; Cengiz Alagoz; Zeynep Alkin; Muhittin Taskapili (Beyoglu Eye Journal, 2017)
INTRODUCTION[|]The aim of this study was to evaluate treatment outcomes of intravitreal dexamethasone implant (IDI) in patients with macular edema (ME) secondary to retinal vein occlusion (RVO), and to assess mean number of visits and injections during 12 months of treatment.[¤]METHODS[|]Records of newly diagnosed RVO patients who were treatment-naïve and had follow-up of at least 12 months were included in this retrospective case series. All patients received initial, single dose of IDI, which was repeated in monthly or bimonthly follow-up when visual acuity decreased by 1 or more lines compared with most recent visit, or an increase in central retinal thickness (CRT) >150 μm was observed in optical coherence tomography images. Primary outcome measures of this study were change in best-corrected visual acuity (BCVA) and CRT. Secondary outcome measures were number of visits and number of injections.[¤]RESULTS[|]Forty-five eyes of 45 patients were included. Mean BCVA at baseline and month 3, 6, 9, and 12 was 0.15+-0.15 decimals, 0.23+-0.24 decimals, 0.20+-0.20 decimals, 0.18+-0.17 decimals, and 0.19+-0.20 decimals, respectively. Mean CRT at baseline, and months 3, 6, 9, and 12 was 599+-111 μm, 388+-137 μm, 421+-142 μm, 409+-130 μm, and 420+-169 μm, respectively. Mean number of planned visits at month 12 was 4.8+-1.0, and number of completed visits was 4.2+-1.0 (89.0% completion). Mean number of planned injections at month 12 was 1.78+-0.7, and number of injections performed was 1.76+-0.7 (98.8% completion).[¤]DISCUSSION AND CONCLUSION[|]IDI did not appear to be effective agent in real-life conditions of treatment of ME secondary to RVO with respect to visual outcomes. Fact that the study consisted of heterogeneous group of patients, as well as small number of cataract operations and injections were likely main reasons for poor visual outcomes. However, IDI did demonstrate significant effect on anatomical outcomes. Number of both visits and injections was lower than observed in prospective multicenter studies, as expected.[¤]